FURTHER DEVELOPMENT OF THE METHODOLOGY OF PREPARING FUTURE ENGINEERS TO SOLVE GENERAL TECHNICAL PROBLEMS FROM PHYSICS TO THE PROFESSION (Neo Science Peer Reviewed Journal, 2023)
In this article, the ideas about the possibility of further development of the methodology of solving general technical problems in the training of future engineers are described.